Seeding Rates and Fertilizer Placement to Improve Strip-Till and No-Till Corn - D. W. Sweeney (Kansas Agricultural Experiment Station Research Reports, 2015)
In 2013, late planting resulted in corn yields that were less than 110 bu/a. Yields were not increased with seeding rates above 26,000/a, but a small increase in yield was obtained with knife applications of fertilizer nitrogen (N) compared with dribble.
Keywords: corn yield; seeding rate; fertilizer placement; strip tillage; no-till